Potential of Metarhizium anisopliae and Beauveria bassiana to control Dinoderus porcellus (Coleoptera: Bostrychidae) infesting yam chips - Loko, Y.; Toffa, J.; Bada, B.; Dassou, A.G.; Zanzana, K.; Gavoedo, D.M.; Adikpeto, J.; Tamò, Manuele (Elsevier, 2022)
The beetle Dinoderus porcellus Lesne is a serious storage insect pest that causes important losses by destroying stocks of yam chips. In the aim to found an alternative control method to the use of synthetic insecticides for its management, the virulence of the entomopathogenic fungi Beauveria bassiana (Balsamo) Vuillemin (isolate Bb115) and Metarhizium anisopliae (Metschnikoff) Sorokin (isolate Met 31) against adults of D. porcellus was evaluated under laboratory conditions (25 ± 2 °C and 70 ± 5% RH). Then, the effectiveness of the most virulent entomopathogenic fungus as biological agent against D. porcellus was assessed under farmer storage conditions. For each entomopathogenic fungus isolate, four conidial concentration (0, 105, 107, and 109 conidia/mL) at the dose of 1 µL were inoculated topically on D. porcellus adults (3–5 days old). Observations focused on insect mortality, cadaver sporulation and weight loss of yam chips. Lethal dose and lethal time values were estimated using probit analysis. Both fungal isolates at all conidial dose caused more than 50% mortality on day 7, with the highest mortality (94.44%) achieved using B. bassiana at the 109 conidia/mL. LT50 values for B. bassiana and M. anisopliae isolates were 2.63 and 3.35 days, respectively, while their LT90 values were 6.15 and 9.87 days, respectively. Yielding the lower LD90 values and the highest rates of cadaver sporulation, B. bassiana isolate appeared as the most virulent against D. porcellus. After 3 months of storage, comparatively to the control, the B. bassiana isolate at the highest conidial dose (109 conidia/mL) significantly reduced D. porcellus populations, and weight loss of yam chips. This study revealed the potential of B. bassiana and M. anisoplae isolates as biological control agent against D. porcellus for yam chips protection.